PENGARUH PEMBERIAN MINYAK GORENG YANG DIFORTIFIKASI VITAMIN A TERHADAP CADANGAN VITAMIN A TUBUH IBU NIFAS - Yuniar Rosmalina; Dewi Permaensih; Tetra Fajarwati; Susilowati Herman (Penelitian Gizi dan Makanan (The Journal of Nutrition and Food Research), 2009)
ABSTRACT Background: The consequences of vitamin A deficiency have been well-known over the country. The status vitamin A depends on the intake of vitamin A source food. Serum retinol is the most commonly used for determination of the vitamin A status. Other method is MRDR method that can directly estimate body stored.The objectives the study was determined the changes of status vitamin A after 90 days intervention by cooking oil fortified by vitamin A 25 ppm.Method: The respondent was mother with breastfeed baby age 14- 28 days. Out of 142 mother were randomly assigned into 4 groups: I. received fortified cooking oil 25 ppm combined with 2 capsules high dose vitamin A (200.000 IU), II received non fortified cooking oil combined with 2 capsules high dose vitamin A (200.000 IU), III received fortified cooking oil 25 ppm combined placebo capsule, IV received non fortified cooking oil combined with placebo capsules. The length of intervention was 90 days. Data collection including characteristic respondent, anthropometric measurement, serum retinol before and after intervention, vitamin A2 before and after intervention, ratio MRDR before and after intervention and vitamin A intake. Results: Body weight, parity, and educational level were no significantly different between groups. Prior to study  showed that serum retinol was no significantly different among groups, group I was 32.8 ±11.52 ug/dl , group II 34.9±11.30 ug/dl, group  III 34.6±12.87 ug/dl, and group IV 33.9±9.96 ug/dl. MRDR ratio also no significantly diffrenet before intervention kelompok group 1 0.0748±0.0586 ug/dl, group II  0.0751±0.0741 ug/dl, group III 0.0850±0.0437 ug/dl, group IV 0.0837±0.0395 ug/dl. After 90 days intervention serum retinol increased in group I,II, and III, while the control group (group IV) was decreased. The change serum retinol was significantly different among groups. The change in group I was 5.30 ug/dl , 3.96 ug/dl in group II, 2.95 ug/dl in group III and - 4.58 ug/dl in group IV. Rasio MRDR (deposit) was significantly different after intervention among group. Deposit vitamin A in group I and III were increased after intervention while in group II and IV were decreased, however there were no significantly different between groups. Conclusion: Distribution cooking oil fortified by vitamin A 25 ppm increased serum retinol after 90 days intervention. Deposit Vitamin A mother who received fortified cooking oil combined with high dose capsules as well as placebo capsules increased after 90 days intervention. [Penel Gizi Makan 2009, 32(2): 137-147]   Key words: fortified cooking oil, breastfeeding mother, retinol, MRDR